2020
DOI: 10.1021/acsomega.0c02113
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Identification of Potential Phosphorylation in the Cytoplasmic Domain of Epithelial Cell Adhesion Molecule

Abstract: The epithelial cell adhesion molecule (EpCAM) is a transmembrane cell adhesion glycoprotein, which primarily contributes to stemness, proliferation, and metastasis properties of tumor cells. Regulated intramembrane proteolysis by ADAM proteases and γ-secretase cleaves EpCAM into an ∼27 kDa soluble extracellular and an ∼4 kDa cytoplasmic domain (EpICD). After the EpICD fragment is released inside the cell, the formation of a nuclear signaling complex with the FHL2 molecule is critical for exerting its regulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
2
2
Order By: Relevance
“…Though many studies have modeled EpCAM [ 3 , 10 , 28 , 29 , 30 , 31 ], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these studies have mostly focused on predicting EpCAM interactions with therapeutics targeting the physiological cis -dimer form [ 10 , 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Though many studies have modeled EpCAM [ 3 , 10 , 28 , 29 , 30 , 31 ], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these studies have mostly focused on predicting EpCAM interactions with therapeutics targeting the physiological cis -dimer form [ 10 , 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 76%
“…Though many studies have modeled EpCAM [3,10,[28][29][30][31], we have not found reported evidence of the TY loop-CTD binding site. This is understandable given that these Fish Fish + HTY ratio of each residue at the CTD site for the fish and fish + HTY systems.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…In acute myeloid leukemia, EpCAM + leukemia cells show augmented chemoresistance and oncogenesis [ 7 ]. Upon proteolytic cleavage by γ-secretase, the intracellular domain of EpCAM interacts with the Wnt signaling pathway (β-catenin, FHL2) and translocates to the nucleus, where it regulates the expression of Myc as well as cyclin A and E [ 8 , 9 ]. Myc, along with NFκB and other regulatory proteins (Sp1, AP2), controls telomerase transcription, which is crucial for uncontrolled proliferation of cancer cells [ 10 ] ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%